Unique role of DDX41, a DEAD-box type RNA helicase, in hematopoiesis and leukemogenesis - Shinriki, Satoru; Matsui, Hirotaka (Frontiers in Oncology, 2022)
In myeloid malignancies including acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS), patient selection and therapeutic strategies are increasingly based on tumor-specific genetic mutations. Among these, mutations in DDX41, which encodes a DEAD-box type RNA helicase, are present in approximately 2–5% of AML and MDS patients; this disease subtype exhibits a distinctive disease phenotype characterized by late age of onset, tendency toward cytopenia in the peripheral blood and bone marrow, a relatively favorable prognosis, and a high frequency of normal karyotypes. Typically, individuals with a loss-of-function germline DDX41 variant in one allele later acquire the p.R525H mutation in the other allele before overt disease manifestation, suggesting that the progressive decrease in DDX41 expression and/or function is involved in myeloid leukemogenesis. RNA helicases play roles in many processes involving RNA metabolism by altering RNA structure and RNA-protein interactions through ATP-dependent helicase activity. A single RNA helicase can play multiple cellular roles, making it difficult to elucidate the mechanisms by which mutations in DDX41 are involved in leukemogenesis. Nevertheless, multiple DDX41 functions have been associated with disease development. The enzyme has been implicated in the regulation of RNA splicing, nucleic acid sensing in the cytoplasm, R-loop resolution, and snoRNA processing. Most of the mutated RNA splicing-related factors in MDS are involved in the recognition and determination of 3' splice sites (SS), although their individual roles are distinct. On the other hand, DDX41 is likely incorporated into the C complex of the spliceosome, which may define a distinctive disease phenotype. This review summarizes the current understanding of how DDX41 is involved in this unique myeloid malignancy.